Ten Recommendations for Food Security Policy Using Bibliometric Analysis Based on Scopus Database - Wawan Purwandi; Yogi Suprayogi Sugandi; Widya Setiabudi (Yayasan Riset dan Pengembangan Intelektual, 2024)
The deterioration of the global food system during COVID-19 particularly in terms of sporadic closures of food processing facilities with adverse consequences for food security and increasing the risk of hunger.The impetus for creating food security arises from the central role of food in human life. One effort to achieve this is through the concept of food self-sufficiency, as a country's ability to meet food needs from domestic production. The preparation of this article utilizes descriptive bibliometric analysis which focuses on literature data banks. Bibliometrics is a quantitative method applied to explore research domains through meta data on articles provided in bibliographic database platforms,This article was written only using the Scopus database. Meta data performed by bibliometrics includes publication titles, keywords, abstracts, and citation notes. This article produces 10 recommendations that need to be carried out by a government, one of which is transforming the food system into an important step to overcome vulnerabilities in the system and increase overall food security.